KETERLIBATAN PEREMPUAN DALAM BERMASYARAKAT: STUDI PADA MASYARAKAT PANTAI KABUPATEN PADANG PARIAMAN - Faridah, Faridah (Humanus, 2012)
This research aims to; (a) identify women’s involvement in the development of nagari (local state), (b) identify community efforts in empowering women to participate in the nagari development, (c) identify the women empowerment programs conducted by related agencies and institutions, (4) indentify the pattern of women empowerment in order to participate in the nagari development, and (5) identify community values that underlie women’s participation in the nagari development. This research is descriptive qualitative. It is conducted in coastal areas of Padang Pariaman regency, represented by each nagari in each of these districts: Ulakan Tapakis, Sungai Limau, Batang Gasan, and Lubuk Alung. Data is collected using questionnaires, interviews, direct observation, and library research. Data is analyzed qualitatively. The result shows that; 1) only a small number of women involves in the nagari development, due to the low level of education, 2) most community’s efforts in empowering women to participate in the nagari development depend only on the information or initiatives by the government whose meetings are part of government programs, 3) women empowerment program is held by the local agencies and institution, 4) women empowerment encouraged by the respondents are held in the coastal areas with coastal tourism, where women are active in coastal-based entrepreneurship, 5) women participation in every aspects of political, social, and cultural development are based on the value adat basandi syarak, syarak basandi kitabullah (traditional value based on the interpretation of the Koran).Key words:  women involvement, participation, development